Omadacycline in the treatment of community-acquired bacterial pneumonia in patients with comorbidities: a post-hoc analysis of the phase 3 OPTIC trial - Rodriguez, George D.; Warren, Nathan; Yashayev, Roman; Chitra, Surya; Amodio-Groton, Maria; Wright, Kelly (Frontiers in Medicine, 2023)
Introduction The 2019 American Thoracic Society/Infectious Disease Society of America guidelines recommend respiratory fluoroquinolones to treat community-acquired bacterial pneumonia (CABP) in adults with comorbidities. Fluoroquinolones are effective against both typical and atypical pathogens. However, fluoroquinolone treatment has a risk of adverse effects, and the Food and Drug Administration has issued black box safety warnings for their use. Inpatient use of fluoroquinolones has reduced as a result; however, most antibiotic courses are completed as outpatients and discharge prescriptions account for the majority of fluoroquinolone use. As such, a new treatment option is needed to replace fluoroquinolones. Omadacycline is an aminomethylcycline antibiotic with a broad spectrum of activity and is available as a once-daily intravenous or bioequivalent oral formulation. Methods This study assessed the safety and clinical efficacy of omadacycline compared with moxifloxacin for the treatment of adult CABP patients with Pneumonia Severity Index (PSI) risk class II/III and ≥1 comorbidity through a post-hoc analysis of the phase 3 OPTIC study (NCT02531438). Results In total, 239 omadacycline- and 222 moxifloxacin-treated patients were assessed. The median age was similar between groups (omadacycline: 57 years; moxifloxacin: 58 years), with 26.0% and 26.6%, respectively, ≥65 years of age. Early clinical response was 91.6% for patients with ≥1 comorbidity treated with omadacycline and 91.4% for those treated with moxifloxacin. Post-treatment evaluation results for overall response were 89.1% in the omadacycline group and 87.4% in the moxifloxacin group. Conclusion Safety warnings have reduced inpatient use of fluoroquinolones; however, outpatient and discharge prescriptions account for the majority of fluoroquinolone use. Outpatients with comorbidities need an efficacious alternative to fluoroquinolones. Omadacycline maintains the similar efficacy and benefits of fluoroquinolones as a once-daily, monotherapy, bioequivalent oral option with potent in vitro activity against the most common CABP pathogens, including S. pneumoniae and atypical pathogens, but offers a materially different safety profile consistent with its tetracycline heritage. In conclusion, both omadacycline and moxifloxacin exhibited similar efficacy in patients with PSI risk class II/III and comorbidities. Omadacycline fulfills an unmet need as an oral monotherapy treatment option for adult patients with CABP, which will further reduce the use of fluoroquinolones. Clinical trial registration https://www.clinicaltrials.gov/study/NCT02531438, identifer: NCT02531438; https://www.clinicaltrialsregister.eu/ctr-search/search?query=2013-004071-13, identifier: EudraCT #2013-004071-13.